Consequences in Infants That Were Intrauterine Growth Restricted - Erich Cosmi; Tiziana Fanelli; Silvia Visentin; Daniele Trevisanuto; Vincenzo Zanardo (Hindawi Limited, 2011)
Intrauterine growth restriction is a condition fetus does not reach its growth potential and associated with perinatal mobility and mortality. Intrauterine growth restriction is caused by placental insufficiency, which determines cardiovascular abnormalities in the fetus. This condition, moreover, should prompt intensive antenatal surveillance of the fetus as well as follow-up of infants that had intrauterine growth restriction as short and long-term sequele should be considered.